2020
DOI: 10.1042/bsr20192794
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a targets Sfrp1 to induce renal fibrosis in diabetic nephropathy by activating Wnt/β-Catenin signalling

Abstract: Diabetic nephropathy (DN) commonly causes end-stage renal disease (ESRD). Increasing evidence indicates that abnormal miRNA expression is tightly associated with chronic kidney disease (CKD). This work aimed to investigate whether miR-27a can promote the occurrence of renal fibrosis in DN by suppressing the expression of secreted frizzled-related protein 1 (Sfrp1) to activate Wnt/β-catenin signalling. Therefore, we assessed the expression levels of miR-27a, Sfrp1, Wnt signalling components, and extracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…We also observed that the WNT/β-catenin pathway was activated: the total protein and nucleoprotein expressions of β-catenin in the HG condition were both higher than those in the NG condition. The same phenomenon was observed in rat kidney cells cultured with high glucose ( 25 ). After the WNT pathway is activated, β-catenin enters the cell nucleus and combines with the transcription factor TCF/LEFs to initiate the transcriptional regulation of multiple target genes, including c-Myc ( 26 ).…”
Section: Discussionsupporting
confidence: 74%
“…We also observed that the WNT/β-catenin pathway was activated: the total protein and nucleoprotein expressions of β-catenin in the HG condition were both higher than those in the NG condition. The same phenomenon was observed in rat kidney cells cultured with high glucose ( 25 ). After the WNT pathway is activated, β-catenin enters the cell nucleus and combines with the transcription factor TCF/LEFs to initiate the transcriptional regulation of multiple target genes, including c-Myc ( 26 ).…”
Section: Discussionsupporting
confidence: 74%
“…22 Several miRs have been reported as fibrosis promoters and underlying prognostic markers in diabetes or diabetes-related complications, such as miR-27a and miR-135a. 23,24 Li et al found that the pathological silencing of miR-32 could improve hepatic fibrosis. 25 However, there was no direct evidence to support the role of miR-32 in DN fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 not only suppresses the inhibitory Smad7 of TGF-β signaling to promote fibrosis (Zhong et al, 2013;Wang et al, 2014) but also targeting the Sprouty (SPRY) to activate the Ras/MEK/ERK signaling to activate fibrogenesis of TGF-β signaling (Xu et al, 2014). In addition, miR-21 also exerts profibrotic and pro-inflammatory Anti/pro-fibrosis (Kato et al, 2007;Chung et al, 2010;Krupa et al, 2010;Kato et al, 2011b;Putta et al, 2012;Deshpande et al, 2013;Ma et al, 2016;Liu et al, 2018) (Zhong et al, 2011;Wang et al, 2013;Zhong et al, 2013;Wang et al, 2014;Lai et al, 2015;Mcclelland et al, 2015;Kölling et al, 2017;Chen et al, 2018) Pro-inflammation miR-27a SFRP1; PRKAA2; PPARγ Pro-fibrosis (Hou et al, 2016;Wu et al, 2018b;Shi et al, 2020) miR-130b TGF-β1; Smad2/3; Smad4 (Castro et al, 2014;Lv et al, 2015;Liu et al, 2019b;Ma et al, 2019b) effects by targeting PTEN, tissue inhibitor of matrix metalloproteinases (TIMPs), and other molecules, as shown in Table 3.…”
Section: Tgf-β/smad-dependent Mirnas In Renal Fibrosis and Inflammation In Dkdmentioning
confidence: 99%